Pengembangan E-Modul Dengan Pendekatan PBL Pada Materi Trigonometri - Saraswati Sidiq, Fitriah; Ralmugiz, Uke; Fatmawati, Agustin; P, Sudirman (JTMT: Journal Tadris Matematika, 2024)
This research aimed to study the process of e-module development using problem based learning (PBL) approaching in trigonometry subject, which is feasible and effective based on students’ responses. This study was research and development using ADDIE model (analyzing, design, development, implementation and evaluation). Data was collected using questionary in 5 scales to study e-module feasibility and using questionary for students to get their responds. Validators here were lecturer and teacher in mathematic learning. Subject here was 28 students Results shows that the e-module is feasible for implementation that indicated by the validation test from content expert in the feasible category (very good), and from media expert in the feasible category (very good). Student respond got very interesting category. The average score for test result was 92, therefore this e-module of trigonometry with PBL approach is effective and feasible for implementation in mathematic learning.